2016
DOI: 10.1021/acs.jchemed.5b00849
|View full text |Cite
|
Sign up to set email alerts
|

Application of Heterogeneous Copper Catalyst in a Continuous Flow Process: Dehydrogenation of Cyclohexanol

Abstract: In this laboratory experiment, the synthesis of a supported solid catalyst (Cu/SiO 2 ) and its application in the dehydrogenation of cyclohexanol performed under flow conditions was studied. The experiment was planned for a group of two or three students for two 6 h long sessions. The copper catalyst was synthesized using incipient wetness impregnation of the silica support with copper(II) nitrate trihydrate as the precursor of the active phase. It was then dried, calcined, and reduced. Each step of the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…3 Ulkowska et al developed a laboratory experiment, which included the synthesis of a heterogeneous copper catalyst and its application in the dehydrogenation of cyclohexanol performed under flow conditions. 4 The sulfur compounds in fuels can convert into SOx when fuel oils are burning and subsequently cause the formation of smog, PM 2.5, and acid rain. Thus, reducing the level of sulfur content in fuel oils has long been desired for environmental reasons.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Ulkowska et al developed a laboratory experiment, which included the synthesis of a heterogeneous copper catalyst and its application in the dehydrogenation of cyclohexanol performed under flow conditions. 4 The sulfur compounds in fuels can convert into SOx when fuel oils are burning and subsequently cause the formation of smog, PM 2.5, and acid rain. Thus, reducing the level of sulfur content in fuel oils has long been desired for environmental reasons.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Tao et al presented an educational experiment for advanced organic chemistry students, in which students prepared a tertiaryamine-functionalized polyacrylonitrile fiber and utilized it as heterogeneous catalyst to synthesize substituted 2-amino-2-chromenes . Ulkowska et al developed a laboratory experiment, which included the synthesis of a heterogeneous copper catalyst and its application in the dehydrogenation of cyclohexanol performed under flow conditions …”
Section: Introductionmentioning
confidence: 99%
“…Catalysis is receiving renewed attention, and catalysts are the core in SCR technology. In this Journal , there are many reports of teaching experiments about the synthesis and applications of catalysts in order to help students gain insight into catalysts, such as Burke et al who introduced using transition-metal complexes as catalysts for radical addition reactions . Malinak et al reported the synthesis and catalytic activity of a vanadium haloperoxidase model complex .…”
Section: Introductionmentioning
confidence: 99%
“…Pertinent examples include experiments in which students fabricate their own multifluidic devices, to other experiments where students exploit existing flow reactors for synthetic or analytical experiments. Some notable examples include a report of the dehydrogenation of cyclohexanol using a heterogeneous copper catalyst in flow, a description of a methylation of 2-naphthol under continuous gas flow conditions, and a report of the synthesis of hydroxymethylfurfural from fructose . Most importantly, a report in 2013 describes experiments designed for laboratories focusing on organic synthesis and provided various examples that demonstrate the advantages of continuous flow versus batch processes to students .…”
Section: Introductionmentioning
confidence: 99%